Implementasi Blended Learning pada Pembelajaran Bahasa Inggris di SD Kebon Dalem 2 Semarang Tahun Akademik 2021/2022 - Tarcisia Sri Suwarti; Siti Lestari; M. Wahyu Widiyanto (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2022)
Learning activities during pandemic covid-19 were implemented using online learning. However, many adjutsments have occured in learning policies during this pandemic. The Ministry of education introducing new learning system namely the blended learning method. This method encourages the digitization of teaching and learning activities. Blended learning involves offline class accompanied by online activities (online class). The problems of this research are 1) How do teachers implement blended learning in teaching English at SD Kebon Dalem 2 Semarang? 2) how do students respond to learning English with blended learning? 3) what are the obstacles teachers and students faced in learning English with blended learning? This research uses a descriptive qualitative method. The subject of the research are the English teacher and  students of SD Kebon Dalem 2 Semarang. The stages of research method are data collection, data classification and data analysis conducted at SD Kebon Dalem 2 Semarang. The output of this research are National ISSN Journal and Prosiding of SNHP UPGRIS. The conclusions of the research are: 1) Blended learning occurs before English learning class preceded by giving instructions via Google classroom and continued by offline class which is held  with online class via Gmeet attended by 50% of students at the same time 2) Students give positive responds about learning English using blended learning which can be seen in the enthusiasm and activeness of students in class, 3) the obstacle faced by the English teacher and students only occur when there is power outage which make the internet connection and the learning process stopped for a moment.